MU'TAQAL Machine: Power, Gender and Identity in Egypt's Political Prisons, 1948-1981 - Ashmawi, HE (2020)
This thesis charts the history and evolution of a mass-incarcerating regime of detention, disappearance and torture in Egypt between 1948 and 1981. In seeking to explain Egypt’s carceral present, it traces, for the first time, the history of the Egyptian Mu‘taqal [political prison], from its emergence as a powerful instrument of government in the aftermath of the Second World War, through to its entrenchment as a mainstay of post-colonial governance by the newly independent state and by successive regimes thereafter.